1991
DOI: 10.1037/0096-1523.17.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Grasping tau.

Abstract: In the present study a direct manipulation of the optical expansion pattern was carried out. What happens to the timing of the grasp movements involved in catching a ball when optical expansion information is not veridically provided? By using 2 luminescent balls of constant size and a luminescent ball that could change its diameter during flight, it was possible to manipulate the rate of optical expansion directly. The results of 2 experiments (binocular vision in Experiment 1 and monocular vision in Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
212
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(224 citation statements)
references
References 24 publications
7
212
3
2
Order By: Relevance
“…However, when such a late occlusion could not be anticipated, specific adaptations of the timing of the grasp were lacking so that grasping time was equal to trials with no occlusion (see Table 1). Such adaptations to the grasping phase of catching contrast with previous work that has reported invariant timing across various task constraints (Savelsbergh et al 1991(Savelsbergh et al , 1993Laurent et al 1994;Bennett et al 1999;Mazyn et al 2006;Tijtgat et al 2010), as well as in the face of perturbations (Polman et al 1996;Button et al 2000;Mazyn et al 2007b), although it has been previously reported at individual level (Button et al , 2002.…”
Section: Discussioncontrasting
confidence: 93%
“…However, when such a late occlusion could not be anticipated, specific adaptations of the timing of the grasp were lacking so that grasping time was equal to trials with no occlusion (see Table 1). Such adaptations to the grasping phase of catching contrast with previous work that has reported invariant timing across various task constraints (Savelsbergh et al 1991(Savelsbergh et al , 1993Laurent et al 1994;Bennett et al 1999;Mazyn et al 2006;Tijtgat et al 2010), as well as in the face of perturbations (Polman et al 1996;Button et al 2000;Mazyn et al 2007b), although it has been previously reported at individual level (Button et al , 2002.…”
Section: Discussioncontrasting
confidence: 93%
“…Even though this hypothesis has been much disputed in recent studies of the control of interceptive actions (e.g., Bootsma et al, 1997;Dessing, Bullock, Peper, & Beek, 2002;Lee et al, 1983;Montagne et al, 2001;Peper, Bootsma, Mestre, & Bakker, 1994;Savelsbergh et al, 1991), it must be the case that the specific characteristics of this task require a prediction, as control of the action is not possible after releasing the ball.…”
Section: Resultsmentioning
confidence: 99%
“…More precisely, the inverse of the relative rate of change of optical angle subtended at the point of observation relates one-to-one to the time remaining before contact (Lee, 1976;Knowles & Carel, 1958). Researchers have argued that tau is exploited by plummeting gannets to dive into water (Lee & Redish, 1981), by somersaulters to land on their feet (Lee, Young, & Rewt, 1992), and that tau can also be exploited to guide interceptive actions like catching balls (e.g., Savelsbergh, Whiting, & Bootsma, 1991). Elegantly, the change of optical angle not only depends on the motion of the point of observation but also on the object's motion.…”
Section: J J Gibson's Theory Of Perception and Its Conception Of Inmentioning
confidence: 99%
“…The search for specifying variables in the ambient array that animals are claimed to use to perceive and act has led to intriguing discoveries (e.g., Amazeen & Turvey, 1996;Savelsbergh et al, 1991).…”
Section: Empirical Studies Of Perception Action Learning and Develmentioning
confidence: 99%